2019
DOI: 10.1001/jamanetworkopen.2019.9782
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness of Housing First Intervention With Intensive Case Management Compared With Treatment as Usual for Homeless Adults With Mental Illness

Abstract: Key Points Question Is a Housing First intervention with Intensive Case Management for homeless people with mental illness cost-effective compared with treatment as usual? Findings In this economic evaluation study of data from the At Home/Chez Soi randomized clinical trial with 1198 initially homeless participants, the incremental cost-effectiveness ratio was $56.08 per additional day of stable housing. At $67 per day of stable housing, there was an 80% ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
(95 reference statements)
1
34
0
3
Order By: Relevance
“…We found 19 studies assessing the cost and net cost of housing interventions. 30,41,45,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145] In some studies, permanent supportive housing interventions were associated with increased cost to the payers, and the costs of the interventions were only partially offset by savings in medical and social services as a result of the intervention. 30,41,[131][132][133][134]142 Six studies showed that these interventions saved payers money.…”
Section: Permanent Supportive Housingmentioning
confidence: 99%
“…We found 19 studies assessing the cost and net cost of housing interventions. 30,41,45,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145] In some studies, permanent supportive housing interventions were associated with increased cost to the payers, and the costs of the interventions were only partially offset by savings in medical and social services as a result of the intervention. 30,41,[131][132][133][134]142 Six studies showed that these interventions saved payers money.…”
Section: Permanent Supportive Housingmentioning
confidence: 99%
“…Logements permanents combinés avec support Nous avons recensé 19 études qui ont évalué le coût et le coût net des interventions axées sur le logement 30,41,45,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145] . Selon certaines, les interventions de type logement permanent combiné avec support (LPCS) ont été associées à une augmentation des coûts pour les payeurs, et les coûts des interventions n'ont été que partiellement compensés par les économies sur le plan des services médicaux et sociaux par suite des interventions 30,41,[131][132][133][134]142 .…”
Section: Répercussions Sur Le Rapport Coût-efficacité Et Les Ressourcesunclassified
“…De plus, 1 analyse coût-utilité sur les LPCS a laissé entendre que la prestation de services liés au logement était associée à une augmentation des coûts et à une augmentation des années de vie ajustées en fonction de la qualité (AVAQ), avec un rapport coût-efficacité différentiel de 62 493 $US par AVAQ 136 . Comparativement aux soins usuels, les LPCS se sont révélés plus coûteux pour la société (coût net 7868 $CA, IC de 95 %, 4409 $ à 11 405 $) 138 .…”
Section: Répercussions Sur Le Rapport Coût-efficacité Et Les Ressourcesunclassified
“…Teaching social skills in the domains of finding and renting an apartment, using time well, getting closer to people, managing finances, avoiding drugs and alcohol problems, solving interpersonal problems, and managing one's health are proposed as an important determinant of housing acquisition and support [25]. The provision of stable housing for homeless adults with mental illness with intensive case management is also likely a cost-effective intervention in comparison with usual treatments [26].…”
Section: Primary Preventionmentioning
confidence: 99%